2019
DOI: 10.1103/physrevfluids.4.083201
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic detonation stabilization in supersonic expanding channels

Abstract: realized through the dynamic control of a moving boundary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…It is found that, for this given expansion angle, detonation sustainment can be maintained in supersonic flows in the same position after the shutdown of the hot jet (Cai et al . 2019).…”
Section: Computational Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that, for this given expansion angle, detonation sustainment can be maintained in supersonic flows in the same position after the shutdown of the hot jet (Cai et al . 2019).…”
Section: Computational Modelmentioning
confidence: 99%
“…It is found that detonation sustainment can be maintained almost in the same position after the shutdown of the hot jet, suggesting that quasi-steady propagation of detonation can be achieved in this case for a given expansion angle; however, it should be noted that normally the quasi-steady state of detonation propagation can only be maintained for a limited time because the detonation may gradually attenuate and finally fail due to the Prandtl–Meyer expansion fan resulting from the expanding wall (Cai et al . 2019). Overall, for the two approaches, the cavity can lead to the formation of an overdriven detonation due to enhancement of pressure oscillations while the quasi-steady state of detonation propagation can be maintained for only a limited time because of the expanding wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al 18 reported that the interaction between the oblique detonation wave and expansion fan induces a new wave structure in the expanding channel. Cai et al 12,19 conducted a numerical simulation of detonation in an expanding channel. They 12,19 demonstrated that the heat release from the combustion of the unburned jet behind the detonation front, promotes dynamic and stable propagation of the detonation wave.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al 12,19 conducted a numerical simulation of detonation in an expanding channel. They 12,19 demonstrated that the heat release from the combustion of the unburned jet behind the detonation front, promotes dynamic and stable propagation of the detonation wave. The rapid jet consumption resulted in appearance of fluctuations and pressure oscillations in the flow field, eventually attenuating the detonation wave.…”
Section: Introductionmentioning
confidence: 99%